PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK PADA MATERI SISTEM TATA SURYA KELAS VI SEKOLAH DASAR - Davina Vina; Filia Prima Artharina; Diana Endah Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the lack of interactive visual media, which makes it difficult for students to understand abstract concepts, particularly the solar system material. Innovative learning media are needed to help students comprehend the material more effectively. The purpose of this study is to determine the results, feasibility, and practicality of the Solar System Pop-Up Book learning media for sixth-grade students at SD Negeri 1 Blimbing. This research uses the Research and Development (R&D) method with the ADDIE model approach (Analysis, Design, Development, Implementation, and Evaluation). The research subjects consisted of 19 sixth-grade students and one sixth-grade teacher at SD Negeri 1 Blimbing. The resulting product is a pop-up book learning media featuring interactive three-dimensional illustrations, equipped with QR codes containing augmented reality (AR), Wordwall interactive quizzes, and links to current news. The media expert validation results obtained a percentage of 93.33%, while the material expert validation results reached 87.5%, with an average of 90.41%, categorized as "Highly Feasible." The teacher response results showed a percentage of 93.33%, and student responses reached 95.45%. Both fall into the "Highly Practical" category. Based on the development results, the Solar System Pop-Up Book learning media developed by the researcher is declared appropriate, feasible, and practical for use in science learning on the solar system material for sixth-grade elementary school students.